Pengaruh DUkungan Keluarga terhadap Status Spiritual Pasien Kanker di RS Dharmais, Jakarta - Petrus Narahawarin; Lucia Utami CB; Fitriana Suprati; Sara Tania Aprianty (Universitas Malahayati Lampung, 2025)
ABSTRACT Total pain experienced by hospitalized terminal patients is a physical, psychological, social and spiritual suffering. A high patient spiritual status can help terminal patients accept their disease condition and reduce the fear and anxiety experienced when facing death. Family support is one of the factors that influence the spiritual status of patients. Forms of family support to terminal patients such as cancer patients can include emotional support, appreciation, practical support, and information. The purpose of this study was to determine the effect of family support on spiritual status in cancer patients in the inpatient room of Dharmais Cancer Hospital Jakarta. The research method used is a quantitative design with a correlative analytic design through a cross sectional approach. The sample in this study was 78 cancer patients using quota sampling technique. The instruments used were family support questionnaires and spiritual status questionnaires. The Spearman Rank correlation test obtained a p-value of 0.005 (0.05) which proved a significant relationship between family support and the spiritual status of cancer patients. Therefore, a structured understanding improvement program is needed for families of cancer patients to increase the participation of all family members in providing attention and support for family members who are under treatment. Keywords: Family Support, Spiritual Status, Cancer Patients, Palliative Care ABSTRAK Nyeri total yang dialami oleh pasien terminal yang dirawat di rumah sakit merupakan penderitaan yang dialami pasien secara fisik, psikologis, sosial, dan spiritual. Status spiritual pasien yang tinggi dapat membantu pasien terminal menerima kondisi penyakitnya dan mengurangi rasa takut dan kecemasan yang dialami ketika menghadapi kematian. Dukungan keluarga merupakan salah satu faktor yang mempengaruhi status spiritual pasien. Bentuk dukungan keluarga kepada pasien terminal seperti pasien kanker dapat mencakup dukungan emosional, penghargaan, dukungan praktis, dan informasi. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh dukungan keluarga terhadap status spiritual pada pasien kanker di ruang rawat inap RS Kanker Dharmais Jakarta. Metode penelitian yang digunakan adalah desain kuantitatif dengan rancangan analitik korelatif melalui pendekatan cross sectional. Sampel pada penelitian ini sebanyak 78 pasien kanker dengan mengunakan teknik quota sampling. Instrumen yang digunakan adalah kuesioner dukungan keluarga dan kuesioner status spiritual. Uji korelasi Spearman Rank didapatkan p-value0,005 (0,05) yang membuktikan adanya hubungan bermakna antara dukungan keluarga dengan status spiritual pasien kanker. Oleh karena diperlukan program peningkatan pemahaman yang terstruktur bagi keluarga penderita kanker untuk meningkatkan peran serta seluruh anggota keluarga dalam memberikan perhatian dan dukungan bagi anggota keluarga yang sedang dalam perawatan. Kata Kunci: Dukungan Keluarga, Status Spiritual, Pasien Kanker, Perawatan Paliatif